تعريف المداخل في المعاجم العربية :‏ ‏المعجم الوسيط نموذجا - أسامة، يعقوب أركيهوصلا
This research studies the Arabic lexicography methods represented in Al-Wasit lexicon of Arabic Language Academy, Cairo, in defining lexical entries, and the scientific in other entries added by the Academy, specifically in scientific terminologies, explaining the lexical definition and its components by mentioning its advantages and disadvantages in explaining the entries. This is done to evaluate this lexicon in the light of modern lexicography. Noting that the lexicography is one of applied linguistics branches, and the issue of definition is one of its critical topics. And the clarity of meaning should be taken into account, most especially in terminological terms, as well as the target group. Taking into account the accuracy of writing the alphabets. The researcher in studying this issue used a descriptive analytical method, relying on lexical sources to determine the foundations and principles adopted in lexicography, whether these foundations and principles are present in Al-Wasit lexicon. The researcher found that the lexicon (Al-Wasit) is classical and modern, that maintains the classical words and introduces modern terminologies. He also found that the lexicon (Al-Wasit) is distinct for being a modern first lexicon despite the fact that it contains some remarks which should be revised.